The Relationship Among Body Composition and Anaerobic Capacity and the Sport Level of Elite Male Motorcycle Speedway Riders - Michalik, Kamil; Szczepan, Stefan; Markowski, Maciej; Zatoń, Marek (Frontiers in Physiology, 2022)
The main objective of this study was to investigate the relationship among anaerobic capacity, body composition, and sport level of junior and senior speedway riders. Sixty riders of professional clubs in Polish top motorcycle speedway league took part in this study. They were divided into two equal groups (n=30): junior (age = 19.7 ± 1.1 yrs) and senior (age = 29.7 ± 5.2). Body composition assessment, Wingate test (WAnT) on cycloergometer, with analysis of acute cardiorespiratory and biochemical responses were performed. Sport level was defined as the number of heats (races) won, winning percentage, total points scored during the season, and average points scored per heat. In statistical evaluation, Student's t test was performed for independent samples and Pearson's linear correlation was calculated. Seniors had higher point ratings indicating sport levels. Juniors differed in BMI by 4% (p<0.01) and fat tissue mass by 20.5% (p<0.01), achieving lower values than seniors. A higher power decrease of 2.3% (p<0.05) in the WAnT test was found in seniors. Body height negatively correlated with all indicators of seniors’ sport level (r= -0.41 to -0.55). Peak power output negatively correlated with seniors’ sport level (r= -0.39 to -0.41). Among the seniors, there was a negative correlation between post-exercise hydrogen ion concentration (r= -0.38), carbon dioxide partial pressure r= -0.45) and average points scored per season. The anthropometric characteristics of body height, lean body mass and body surface area, are significantly correlated with the sport levels of the motorcycle speedway riders. When selecting motorcycle speedway riders, use of these anthropometric characteristics may aid in determining the riders with the most potential to be successful. Metabolic acidosis tolerance and gas exchange efficiency show significance in seniors, indicating the need for intense exercise sessions.